Valence and Core-Level X-ray Photoelectron Spectroscopy of a Liquid Ammonia Microjet - Buttersack, Tillmann; Mason, Philip E; McMullen, Ryan S; Martinek, Tomas; Brezina, Krystof; Hein, Dennis; Ali, Hebatallah; Kolbeck, Claudia; Schewe, Christian; Malerz, Sebastian; Winter, Bernd; Seidel, Robert; et al. (Journal of the American Chemical Society, 2019)
Photoelectron spectroscopy of microjets expanded into vacuum allows access to orbital energies for solute or solvent molecules in the liquid phase. Microjets of water, acetonitrile and alcohols have previously been studied; however, it has been unclear whether jets of low temperature molecular solvents could be realized. Here we demonstrate a stable 20 μm jet of liquid ammonia (-60 °C) in a vacuum, which we use to record both valence and core-level band photoelectron spectra using soft X-ray synchrotron radiation. Significant shifts from isolated ammonia in the gas-phase are observed, as is the liquid-phase photoelectron angular anisotropy. Comparisons with spectra of ammonia in clusters and the solid phase, as well as spectra for water in various phases potentially reveal how hydrogen bonding is reflected in the condensed phase electronic structure.